Voluntary feed intake, growth, rumen fermentation and nutrient utilization in different breeds of Indian goats reared under intensive system - DUTTA, T K; SINGH, N P (The Indian Journal of Animal Sciences, 2011)
Weaned male kids (24) of Barbari (T1, 111.38±2.40 days, 10.80±0.32 kg BW), Jamunapari (T2, 110.87±1.11 days, 11.04±0.50 kg BW) and Marwari (T3, 109.00±1.57days, 11.56±0.71 kg BW) breeds were randomly divided into 3 treatment groups to investigate the response of feed based on agro-industrial by-products and new feed resources [Albizia lebbec (siras) pod-with seed and Vigna sinensis (cowpea) pod-without seed] on growth, rumen fermentation, nutrient utilization and economics of feeding. Concentrate mixture and dry fodder mixture (pigeon pea straw 78.34%, cowpea pods-without seeds 8.33%, coarsely ground siras pod-with seeds 13.33%) were mixed in the ratio of 40:60 and offered ad lib. to the kids under the 3 groups. Limited quantity (300 g/h/d) of available green fodder (lucerne fodder) and berseem hay (100 g/h/d) was offered to all the kids irrespective of treatment groups. DM intake/kg W0.75 was higher in T2 than other 2 groups. ADG and FCE% (gain/DMI) were statistically insignificant among groups. VFA concentation was similar in the breeds during middle and last stage of growth. NH3–N concentration (mg/dl SRL) was significantly higher in T1 and T3 breeds than T2 breed during last stage of growth, whereas, it was similar among the 3 breeds during mid collection. TDN and DCP intake/kg W0.75 varied in different treatment groups. Growth rate in Barbari kids was normal under this feeding regimen, whereas, Jamunapari and Marwari kids grew lower under the same feeding schedule due to lower intake of TDN and DCP. The variations in nitrogen balance and nitrogen balance/kg W0.75 were statistically insignificant among the 3 groups. Therefore, it may be concluded that rations prepared with agro-industrial by-products and new feed resources (siras pod-with seed and cowpea pod-without seed) were effective in Barbari kids, whereas, Jamunapari and Marwari kids grew at lower rate.